Memahami qirāat al-qurān: Ragam bacaan dan signifikansinya dalam ilmu al-qur`ān - Deka Asdinata, Bagus Ardiansyah (Maliki Interdisciplinary Journal, 2025)
Qirāat al-Qurān is a specialized discipline within Qur’anic studies that focuses on the various recitations of the Qur’an transmitted authentically from the Prophet Muhammad (peace be upon him) through the Companions, the Tābi‘īn, and the recognized Imams of Qirāat. Differences in Qirāat emerged due to regional Arabic dialects, diverse methods of transmission, and the historical codification of the Qur’anic text during the era of the Companions. Qirāat are categorized into levels such as Mutawātir, Mashhūrah, Āhād, and Shādhdhah, with seven to ten canonical recitations accepted within the Islamic scholarly tradition. Variations in Qirāat include differences in pronunciation, grammatical structures, and lexical choices, which may influence the interpretation and legal derivation (istinbāṭ) of Qur’anic rulings. Thus, the science of Qirāat plays a crucial role in preserving the originality and integrity of the Qur’anic text, while also serving as a key tool in exegesis (tafsīr) and Islamic jurisprudence (fiqh). Moreover, it aids in the preservation of authentic recitation chains (sanad), understanding the rules of Rasm ‘Uthmānī, and deepening spiritual engagement with the Qur’an. Therefore, studying Qirāat is not merely a technical exercise but a significant aspect of safeguarding the Divine Revelation as an enduring and authentic legacy of Islamic civilization.